2020
DOI: 10.1177/0950017020936872
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Quality of Sex Work

Abstract: This article presents descriptive findings on sex workers’ structural disadvantage and their evaluation of the quality of their work, relative to their other jobs. In-person interviews were conducted in 2013 with sex workers ( n = 218) from Canada. Participants reported they experience precarity (i.e. uncertainty and instability) in employment and other domains of their lives. Compared to the work quality of their other jobs, the majority said sex work was more satisfying and granted greater control and money.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
(80 reference statements)
0
28
0
Order By: Relevance
“…Our study builds on our previous research that compared sex work to other jobs sex workers were doing concurrently (Benoit et al 2020b) and that compared it to related occupations (Benoit et al 2015a(Benoit et al , 2015b. This study added to those studies by examining a variety of work attributes common to two frontline service jobs: hairstyling and sex work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study builds on our previous research that compared sex work to other jobs sex workers were doing concurrently (Benoit et al 2020b) and that compared it to related occupations (Benoit et al 2015a(Benoit et al , 2015b. This study added to those studies by examining a variety of work attributes common to two frontline service jobs: hairstyling and sex work.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this research has largely ignored sex work. There is a growing literature showing the value of examining sex work as an economic activity that involves the performance of various forms of labor for economic returns (Benoit et al 2017(Benoit et al , 2020bRosen and Venkatesh 2008;Sanders 2005). Meanwhile, several studies have suggested links between sex work and mental health ( Krumrei-Mancuso 2017; Puri et al 2017;Treloar et al 2021;Vanwesenbeeck 2005) but have focused on stigma and mistreatment by others and have typically ignored work attributes that are not uniquely associated with sex work (Benoit et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations